Território de esperança: tramas territoriais da agricultura familiar na comunidade rural São Domingos em Catalão (GO) - Venâncio, Marcelo (2008)
The Brazilian agrarian space suffered notable transformations during the after War with the implantation of the politics of modernization brought from the United States of America to the rural place. These politics being thought from the outside to the inside, came full of prejudices, where there mentor had as a goal saving the rural populations in relation to its decay. In this way, they stopped the advancement of the socialism publicity. With this producer character, these politics of modernization began getting effects. With the incorporation to the producers process of technological innovations and the creation of CAIs. With the incentive of the Brazilian State, the modernization got just the proprietors who disposed the funds and big extensions of lands, increasing even more the concentration of big lands on the hands of a minority and, consequently, the enlargement of the social conflicts because of the rural proprieties. In the municipal district of Catalão(GO), the modernization of the agriculture materialized itself from the arrival of paulistas and sulistas who, with the high investments of the State, began producing on the areas of chapada . The important, in this process, is how the familiar agriculture survives under this unfavorable condition to the reproduction. This producers group finds itself in disadvantage, in the same way on the production and on the trading of this products. In this context, in the rural community of São Domingos into the municipal district of Catalão, the minor producers, in a way to get improvements into their income, diversify the production. One part of the products is designated, exclusively, to the familiar consumption and the other is traded on street markets and on the local and regional commerce. These producers keep some cultural characteristics of centuries: parties, mass, collective work, relationship into the neighborhood and relationship like godfather that, even into lots of transformations, are transmitted from parents to the children. With such territorial characteristics, the goal of this research is to comprehend the political, economical and cultural importance of the familiar agriculture into the rural community of São Domingos in Catalão (GO) from the of this territory on. To get this goal, we made researches of field accompanish by readings about this subject and information survey in public departaments as Agenciarural and IBGE.